Totally Laparoscopic Blumgart pancreaticojejunostomy in pancreaticoduodenectomy: initial experience from a tertiary center - Tran Cong, Duy Long; Nguyen, Quoc Thanh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Background: Postoperative pancreatic fistula (POPF) remains the most critical complication following pancreaticoduodenectomy, particularly in minimally invasive pancreaticoduodenectomy (MIPD), where reconstruction is technically demanding. The Blumgart pancreaticojejunostomy has been increasingly adopted due to its potential advantages in reducing anastomotic tension and improving stability. This study aimed to describe a standardized totally laparoscopic Blumgart pancreaticojejunostomy technique and evaluate its early outcomes. Methods: A retrospective descriptive study was conducted including all consecutive patients who underwent MIPD with laparoscopic Blumgart pancreaticojejunostomy at University Medical Center in Ho Chi Minh city between January 2024 and March 2026. Clinical data were obtained from a prospectively maintained database. Perioperative outcomes and postoperative complications were analyzed, with POPF defined according to the International Study Group of Pancreatic Surgery (ISGPS) criteria. Results: A total of 40 patients were included. The cohort consisted predominantly of middle-aged patients with acceptable preoperative status, and most were classified as low risk for POPF. The laparoscopic Blumgart pancreaticojejunostomy was successfully completed in all cases. The median pancreaticojejunostomy time was 85 minutes within a median overall operative time of 346 minutes. Postoperative recovery was generally favorable, with early resumption of oral intake and a median hospital stay of 11 days. Major complications occurred in 5.0% of patients. Clinically relevant POPF was observed in 7.5% of cases, with no reoperation required. Conclusions: A standardized totally laparoscopic Blumgart pancreaticojejunostomy is feasible and reproducible in pancreaticoduodenectomy, with acceptable operative time and favorable short-term outcomes. Standardization of technique and a dedicated surgical team may play a key role in achieving consistent results during the early adoption phase.